Correction: Corrigendum: A brain-sparing diphtheria toxin for chemical genetic ablation of peripheral cell lineages - Mafalda M. A. Pereira (Nature Portfolio, 2017)
Nature Communications 8: Article number: 14967 (2017); Published 3 April 2017; Updated 17 May 2017 The financial support for this Article was not fully acknowledged. The Acknowledgements should have included the following: [***Human Frontiers Science Program (HFSP) funds the labs of A.I.D. and P.C. ***].